The Pseudogenes of Barley - Prade, Verena M.; Gundlach, Heidrun; Twardzick, Sven; Chapman, Brett; Tan, Cong; Langridge, Peter; Schulman, Alan H.; Stein, Nils; Waugh, Robbie; Zhang, Guoping; Platzer, Matthias; Li, Chengdao; et al. (Wiley Blackwell, 2018)
Pseudogenes have a reputation of being ‘evolutionary relics’ or ‘junk DNA’. While they are well characterized in mammals, studies in more complex plant genomes were so far hampered by the absence of reference genome sequences. Barley is one of the economically most important cereals and has a genome size of 5.1 Gb. With the first high-quality genome reference assembly available for a Triticeae crop, we conducted a whole genome assessment of pseudogenes on the barley genome. We identified, characterized, and classified 89,440 gene fragments and pseudogenes, scattered along the chromosomes with occasional hotspots and higher densities at the chromosome ends. Full-length pseudogenes (11,015) have preferentially retained their exon-intron structure. Retrotransposition of processed mRNAs only plays a marginal role in their creation. However, the distribution of retroposed pseudogenes reflects the Rabl configuration of barley chromosomes and thus hints towards founding mechanisms. While defense-response related parent genes were found under-represented in cultivated barley, we detected several defense related pseudogenes in wild barley accessions. 7.2% of the pseudogenes are transcriptionally active and may potentially adopt new regulatory roles.The barley genome is rich in pseudogenes and small gene fragments mainly located towards chromosome tips or as tandemly repeated units. Our results indicate non-random duplication and pseudogenization preferences and improve our understanding of gene birth and death dynamics in large plant genomes and the mechanisms that lead to evolutionary innovations
Keywords: gene fragments; gene evolution; pseudogenes; barley; Hordeum vulgare; plants